RESEARCH OPPORTUNITIES ABOUT MEASURING AGILITY IN SOFTWARE DEVELOPMENT: A CONSTRUCTIVIST PERSPECTIVE/OPORTUNIDADES DE PESQUISA SOBRE MENSURACAO DE A GILIDADE NO DESENVOLVIMENTO DE SOFTWARE: UMA PERSPECTIVA CONSTRUTIVISTA - Lacerda, Rogério Tadeu de Oliveira; Calvetti, Ewerton Sacco; Bernardes, Mayara Lucia; Silveira, Júlia Fraga Cargnin da (Revista de Gestão e Projetos, 2020)
This paper investigates research opportunities in an agile software development process according to constructivist performance evaluation lenses, based on a portfolio of 24 scientific articles relevant to the topic. The instrument used to carry out the systemic analysis was the Proknow-C method (Knowledge Development Process - Constructivist). It was observed in the portfolio that the performance evaluation to measure agility in the context of software development has focused practically on critical success factors and on inflexible models that rank in maturity levels, but without clearly evaluating how much agility is employed. This study addresses relevant research opportunities that seek to identify criteria and to build performance scales for measuring agility based on the values and preferences of the decision makers, who wish to implement the agile philosophy, aligned with the specific strategic of the decision makers objectives and using their singular resources, competences and own organizational culture in order to improve their software development process.